1977
DOI: 10.1002/pol.1977.170150114
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of acrylamide onto methyl cellulose by persulfate ion

Abstract: SynopsisAcrylamide was grafted onto methyl cellulose backbone by using potassium persulfate as initiator in aqueous solution, and variables affecting the copolymerization were studied. It was found that efficiency of grafting was maximum at an initiator concentration of 3.7 X mole/l. Grafting was found to increase steadily with increase in monomer/polymer ratio and with temperature up to 40°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Graft copolymerization of vinyl monomers were done by many workers [14][15][16][17][18][19][20]. The use of persulfate radicals for the grafting of vinyl monomers on natural polymers has been studied [21,22] to get the desired grafting ratio, wherein it was shown that reaction could occur between KSO 4 radical and polysaccharide to form radicals on the polymer backbone directly.…”
Section: Introductionmentioning
confidence: 99%
“…Graft copolymerization of vinyl monomers were done by many workers [14][15][16][17][18][19][20]. The use of persulfate radicals for the grafting of vinyl monomers on natural polymers has been studied [21,22] to get the desired grafting ratio, wherein it was shown that reaction could occur between KSO 4 radical and polysaccharide to form radicals on the polymer backbone directly.…”
Section: Introductionmentioning
confidence: 99%
“…Number of studies8–10 have been done on graft copolymerization of vinyl monomers as methyl methacrylate on curdlan, N ‐vinyl pyrrolidone on gelatin, methyl acrylate (MA) on potato starch, MA on sago starch, vinyl pyrrolidone on chitosan, etc. The use of persulfate radicals for the grafting of vinyl monomers on natural polymers has been studied11, 12 to get the desired grafting ratio, wherein it was shown that reaction could occur between KSO 4 radical and polysaccharide to form radicals on the polymer backbone directly. Lokhande et al13 reported the graft copolymerization of acrylonitrile on GG through (γ‐radiation.…”
Section: Introductionmentioning
confidence: 99%
“…A significant amount of literature refers to the graft copolymerization of vinyl monomers onto it. Ceric ions1–6 and potassium (mono)persulfate7–10 are extensively used to form cellulose radicals directly in graft copolymerization of vinyl monomers on cellulosic materials. Another method to grafting of cellulose is based on the preliminary reaction between OH cellulosic groups and (meth)acryloyl chloride to form cellulose with a certain number of pendant double bonds 11–14.…”
Section: Introductionmentioning
confidence: 99%